Single Local Application of TGF-β Promotes a Proregenerative State Throughout a Chronically Injured Nerve. Issue 6 (21st July 2017) - Sulaiman, Wale; Dreesen, Thomas; Nguyen, Doan
Abstract: BACKGROUND: The lack of nerve regeneration and functional recovery occurs frequently when injuries involve large nerve trunks because insufficient mature axons reach their targets in the distal stump and because of the loss of neurotrophic support, primarily from Schwann cells (SCs). OBJECTIVE: To investigate whether a single application of transforming growth factor-beta (TGF-β) plus forskolin or forskolin alone can promote and support axonal regeneration through the distal nerve stump. METHODS: Using a delayed repair rat model of nerve injury, we transected the tibial nerve. After 8 wk, end-to-end repair was done and the repair site was treated with saline, forskolin, or TGF- β plus forskolin. After 6 wk, nerve sections consisting of the proximal stump, distal to the site of repair, and the most distal part of the nerve stump were removed for nerve histology, axon counts, and immunohistochemistry for activated SCs (S100), macrophages (CD68), cell proliferation (Ki67), p75NGFR, and apoptosis (activated caspase-3). RESULTS: TGF-β plus forskolin significantly increased the numbers of axons regenerated distal to the repair site and the most distal nerve sections. Both treatments significantly increased the numbers of axons regenerated in the most distal nerve sections compared to saline treated. Both treatments exhibited extended expression of regeneration-associated marker proteins. CONCLUSION: TGF-β plus forskolin treatment of chronically injured nerve improved axonal regeneration and increased expression of regeneration-associated proteins beyond the repair site. This suggests that a single application at the site of repair has mitogenic effects that extended distally and may potentially overcome the decrease in regenerated axon over long distance.